Efectividad del programa "alimentando al bebe" en el nivel de conocimiento sobre lactancia materna en primigestas. La Esperanza - 2016 - Villanueva De La Cruz, Ingrid Fiorela (2016)
pre-experimental research was conducted at the "Jerusalem" Hospital - La Esperanza, in the 2016, in order to determine the effectiveness of the program "Feeding your baby" on the level of knowledge about breastfeeding primigestas. The sample consisted of 35 primiparous who met the inclusion criteria. the instrument was used for data collection: Scale to measure the level of knowledge about breastfeeding. The information obtained was processed in the IBM SPSS version 23 STATISTICS and analyzed by statistical test "T-Student". The results are presented in statistical tables single and double entry. After the analysis concludes: 54.7% of primiparous showed a low level of knowledge about breastfeeding before the implementation of the educational program. 80% of first time showed a high level of knowledge about breastfeeding after the implementation of the educational program. The program was significant to increase the level of knowledge about breastfeeding in primipara (p = 0.0), and efficient because it increases the level of knowledge by 67% accepting the true hypothesis.